Financial Analysis of Botanical Pesticides Application in Big White Ginger Farming System (Case Study in Tanjungkerta, Sumedang) - NFN Ermiati (Buletin Penelitian Tanaman Rempah dan Obat, 2017)
Botanical pesticides is generally applied to control plant pest in organic farming systems and ginger farmers in Sumedang commonly used it in ginger cultivation. The study aimed to assess the financial feasibility and sensitivity of botanical pesticide use in big white ginger (JPB) cultivation in Tanjungkerta-Sumedang, West Java. Research was conducted in November 2013 with survey method.  Price was analyzed by converting the input and output to the price applicable in June 2017. Farmer respondents were determined randomly by selecting 20 respondents from 33 farmers of Gemahrita Farmer Group. The financial feasibility was assessed using Net Present Value (NPV), Benefit Cost Ratio (B/C) and Internal Rate of Return (IRR) analysis. Farming sensitivity was measured with  BEP (Break Event Point) of production and price.  Pest and diseases found in ginger plantation were leaf spot (Phyllosticta sp.) and ladybug (Epilachna sp), which were controlled by botanical pesticide made by the farmers from greater galangal, citronella, neem leaf and betle vein leaf. The use of natural pesticides was financially feasible with the eligibility criteria of NPV>0 (Rp 32,081,221,-), B/C Ratio >1 (2.15)  and IRR 13 % above  the prevailing bank rate (1.5% per month). BEP production 9,601 kg.ha-1, BEP price Rp. 1,279,-/kg, 57% below actual productivity and price.  This indicated if there was decrease in productivity and price of ginger <57%, JPB farming system using botanical pesticide was still feasible. JPB farming system using self-made botanical pesticide proved profitable, environmentally friendly and safe for farmer health, hence appropriate and advantageous to be developed.